Klammt open elastic activator and twin blocks in Class II malocclusion treatment. - Eduardo Maikel Curbeira Hernández; Clotilde de la Caridad Mora Pérez (Medisur)
Background: Klammt open elastic activator and twin blocks have been two of the most worldwide studied functional appliances; however, there are different opinions about their effect on the cranium-facial complex. Objective: To determine the efficacy of these appliances in the functional treatment in Class II division I syndrome in early mixed teething. Methods: Prospective, cuasi experimental, “before-after” study without control group, including all children between 6 and 9 years of Area II in Cienfuegos municipality. After applying inclusion criteria, 20 patients were selected through simple randomized sampling and distributed in two groups, one for each technique. Lateral cranium teleradiographies were taken at the beginning and after a year of treatment, and lineal and/or angular measurements of Steiner, Ricketts, McNamara and Legan Burstone cephalograms were applied. Results: Favourable changes in cranium lateral radiographies measurements were obtained mainly from therapy with twin blocks. There was a decrease in the angle formed by the joint planes nasion-point A and nasion-point B and facial convexity, increase in mandible length and inferior facial height. Nasolabial angle and labial protuberance didn´t increase significantly. Conclusions: treated patients positively modified their bio-typology, and growth trend showed positive variations during functional therapy.